Home Health Use Following a Cancer Diagnosis Among Patients Enrolled in Medicare Advantage and Traditional Medicare: Findings From the Newly Linked SEER-Medicare and Home Health OASIS Data. Issue 55 (15th May 2020) - Thomas, Kali S; Schwartz, Margot L; Boyd, Eric; White, Dolly P; Mariotto, Angela B; Barrett, Michael J; Warren, Joan L
Abstract: Background: This article describes characteristics of patients receiving home health following an initial cancer diagnosis, comparing those enrolled in Medicare Advantage (MA) and Traditional Medicare (TM), using the newly linked 2010–2014 National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER)-Medicare and home health Outcome and Assessment Information Set (OASIS) data. Methods: We identified SEER-Medicare beneficiaries with at least one OASIS assessment within 3 months of cancer diagnosis in 2010-2014, and summarized their demographic and clinical characteristics. Demographic and diagnostic data were obtained from the SEER-Medicare data, while further details about cognitive status, mood, function, and medical history were obtained from OASIS. We assessed differences between MA and TM beneficiaries using chi-square tests for independence, t-tests, and Kruskal-Wallis tests. Resutls: We identified 104 023 patients who received home health within 3 months of cancer diagnosis: 81 587 enrolled in TM and 22 436 enrolled in MA. TM cancer patients had higher unadjusted rates of home health use than MA patients (16.3% vs 10.3%, P < .001). TM cancer patients receiving home health had more limitations in their cognitive function than their MA counterparts and longer lengths of service (mean = 42.2 days vs 39.4 days, P < .001; median = 27 vs 26 days, interquartile range = 42). Conclusion: This study demonstrates the large number of cancer patients in the SEER-Medicare-OASIS data and describes characteristics for TM and MA patients. These newly linked data can be used to assess home health care among older patients with cancer.